EVALUATION OF CHANGES IN THE REPORTING SYSTEM OF FOREIGNERS IN IMPROVING IMMIGRATION SUPERVISION AT THE IMMIGRATION OFFICE OF CLASS I NON TPI BOGOR - Adam Firdaus (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2019)
Abstract The Foreigners Reporting Application is an online application system that is useful to help and make an ease of foreigners reporting process. For immigration officials, this application can be used as one of data or information in foreigners supervision. A lot of people do not know the purpose of this, including the immigration officials, even some of them think that this application just makes an extra work and waste time. This study aims to determine the benefits of Foreign Reporting Applications in assisting the implementation of foreigners supervision and how the constraints faced in the implementation of Foreign Reporting Applications. The method used is empirical juridical by conducting field research at the Directorate General of Immigration. The results showed that for various reason, hotels/homestays or individual do not run this application, whereas by registering and fill reporting format in the application, they do not have report their guests or visitors to the immigration office, manually. Moreover, immigration offices have not carried out pro-justice, yet to the owners of hotels/homestays or individual that do not do registration, so it does not cause deterrent effect.